1987
DOI: 10.1203/00006450-198709000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability during Respiratory Pauses in Puppies and Dogs

Abstract: De [~ur~mrrztt c~/'Pm/rutrrc~.c (Pulrnonury Dirr.cion) I tot, total respiratory max(RR), maximum R R interval within a respiratory cycle min(RR), minimum R R interval within a respiratory cycle range(RR), difference between min(RR) and max(RR) NTS, nucleus tractus solitarius N A , nucleus ambiguus V M N , vagal motoneuronsnumber of years (3). We have demonstrated previously that HRV is abnormal in certain groups of infants who are at risk of sudden death (4, 5) and more recently, it as been shown that HRV c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It should also be noted that the feeding episode occurs after an episode of active sleep (and awakening), a sleep stage during which sympathetic outflow is dominant (13). Several authors (14, 15, 16) have shown that physiological events occurring in an active sleep episode just before awakening are characterized by an increase of activation level (increase of body motility and respiratory and cardiac frequencies). Unfortunately, these authors have never related these events to a possible sympathetic outflow that could be integrated to a thermoregulatory food intake episode.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that the feeding episode occurs after an episode of active sleep (and awakening), a sleep stage during which sympathetic outflow is dominant (13). Several authors (14, 15, 16) have shown that physiological events occurring in an active sleep episode just before awakening are characterized by an increase of activation level (increase of body motility and respiratory and cardiac frequencies). Unfortunately, these authors have never related these events to a possible sympathetic outflow that could be integrated to a thermoregulatory food intake episode.…”
Section: Discussionmentioning
confidence: 99%
“…* Many neurological and psychological investigations have used HRV to evaluate the effects of stress, emotion, and work on the autonomic nervous s y~t e r n ,~-l~ including very specialized investigations. l 4 Quantification of HRV has also been used as the standard for evaluating other psychological methods. I 5 Physiological studies in humans have reported an increase of HRV, interpreted as an increase of cardiac va- gal tone at rest, following intensive exercise for several days.…”
Section: Physiology Of Heart Rate Variabilitymentioning
confidence: 99%
“…Bradycardia often starts during the early stages of apnoea, however, and most authors now consider that a reflex response is more likely.2 6 7 Our group originally postulated that reflex bradycardia was most commonly related to respiratory effort against a closed glottis during upper airway obstruction.7 This view has been challenged by Henderson-Smart et al, who suggested a peripheral chemoreceptor response to falling oxygen saturation (Sao2) was the most likely explanation.8 Experiments on immature animals, however, have shown that heart rate changes occur at the beginning of respiratory pauses before any change in arterial blood gases. 9 Oxygenation would appear to exert an important influence, though. We have recently reported that initial Sao2 before the onset of apnoea is significantly lower in those episodes which result in bradycardia.…”
mentioning
confidence: 99%